RETRACTED: Awan et al. The Enhanced Cytotoxic and Pro-Apoptotic Effects of Optimized Simvastatin-Loaded Emulsomes on MCF-7 Breast Cancer Cells. Pharmaceutics 2020, 12, 597 - Zuhier A. Awan; Usama A. Fahmy; Shaimaa M. Badr-Eldin; Tarek S. Ibrahim; Hani Z. Asfour; Mohammed W. Al-Rabia; Anas Alfarsi; Nabil A. Alhakamy; Wesam H. Abdulaal; Hadeel Al Sadoun; Nawal Helmi; Ahmad O. Noor; et al. (MDPI AG, 2024)
The journal retracts the article, "The Enhanced Cytotoxic and Pro-Apoptotic Effects of Optimized Simvastatin-Loaded Emulsomes on MCF-7 Breast Cancer Cells" [...]